2021
DOI: 10.1097/rti.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Primary Lung Cancer

Abstract: Purpose: Primary lung cancers associated with cystic airspaces are increasingly being recognized; however, there is a paucity of data on their natural history. We aimed to evaluate the prevalence, pathologic, and imaging characteristics of cystic lung cancer in a regional thoracic surgery center with a focus on the evolution of computed tomography morphology over time.Materials and Methods: Consecutive patients referred for potential surgical management of primary lung cancer between January 2016 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…Moreover, the incidence of CCLC was estimated at 0.46% in a surgical series (15). However, Byrne et al recently reported an incidence rate of 9.3% in a surgical series (11). In the present study, the incidence of CCLC was higher than previous reports.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Moreover, the incidence of CCLC was estimated at 0.46% in a surgical series (15). However, Byrne et al recently reported an incidence rate of 9.3% in a surgical series (11). In the present study, the incidence of CCLC was higher than previous reports.…”
Section: Discussioncontrasting
confidence: 72%
“…In high-risk individuals, CT screening for lung cancer focuses on early detection; however, there are no detailed CT findings in patients with CCLC. Currently, there are no recommendations or clinical guidelines for the surveillance of CCLC in routine practice or screening (11). Few studies on CCLC have investigated the findings of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET); however, even when findings are available, the number of patients is relatively small (4,5).…”
Section: Introductionmentioning
confidence: 99%